Small animal regional anesthesia and analgesia - Read, Matt R.; Campoy, Luis MRCVS; Fischer, Berit (Berit L.) (Hoboken, New Jersey John Wiley & Sons, Ltd., 2024)
"Small Animal Regional Anesthesia and Analgesia, Second Edition expands and updates the information in the first edition, making this a truly comprehensive and practical reference for regional anesthetic techniques in dogs and cats. Written by leading international experts in the field, this book provides an authoritative yet practical guide to using ultrasound-guided local and regional anesthesia techniques in clinical practice. Grounded in the latest scientific literature, the book presents a wealth of new or updated information, and incorporates a logical, standardized format and high-quality color images, making it easier and faster to find information about each block"--
Ultrasound guidance : The inevitable evolution of locoregional anesthesia / Berit Fischer -- Use of ultrasound for locoregional anesthesia / Matt Read, Micheal O Cathasaigh and Luis Campoy -- How to document the use of locoregional anesthesia in the medical record / Eric Brumberger and Luis Campoy -- Local anesthetic pharmacology / Manuel Martin-Flores and Matias Lorenzutti -- The Eye / Yael Shilo-Benjamini and Peter Pascoe -- Ultrasound-guided Blocks for the Ear / Luis Campoy and Jaime Viscasillas -- Ultrasound-guided Brachial Plexus Block (subscalene approach) / Pablo Otero -- Ultrasound-guided Brachial Plexus Block (Axillary approach) / Luis Campoy -- Ultrasound-guided Proximal RUMM Block (Axillary sheath) / Matt Read -- Ultrasound-guided (distal) RUMM Block / Matt Read and Luis Campoy -- The thoracic spinal nerves : Overview and functional anatomy / Diego Portela and Marta Romano -- Introduction to Fascial Plane Blocks / Berit L. Fischer -- Ultrasound-guided Thoracic Paravertebral Block / Diego A. Portela -- Ultrasound-guided Intercostal Nerve Block / Alexander C.S. Thomson -- Ultrasound-guided Serratus Plane Block / Matt Read -- Ultrasound-guided Parasternal Blocks / Matt Read -- Ultrasound-guided Erector Spinae Plane Block / Tatiana H. Ferreira -- Ultrasound-guided Quadratus Lumborum Block / Marta Garbin -- Ultrasound-guided Transversus Abdominis Plane (TAP) Block / Marta Romano -- Ultrasound-guided Rectus Sheath Block / Tatiana H. Ferreira -- Ultrasound-guided Femoral Nerve Block (Psoas Compartment Block) / Stephan Mahler -- Ultrasound-guided Femoral Nerve Block (inguinal approach) / Luis Campoy -- Ultrasound-guided Saphenous Nerve Block / Luis Campoy -- Ultrasound-guided Parasacral Lumbosacral Trunk Block / Diego A. Portela -- Ultrasound-guided Sciatic Nerve Block (caudal approach) / Luis Campoy -- Ultrasound-guided Pudendal Nerve Block in male cats / Chiara Adami -- Ultrasound-assisted Epidural Anesthesia / Berit Fischer, Matt Read and Luis Campoy -- Complications associated with locoregional anesthesia / Berit L. Fischer.
Includes index.
Keywords: Veterinary anesthesia